Предмет: Алгебра, автор: bella772

Ответьте на вопросы пожалуйста, очень нужно, экзамены на носу, не проходите!!!!
Даю 15 баллов!!

Приложения:

Ответы

Автор ответа: dend1mon
0
 \frac{1*6-1(x^{2}-1) }{(x^{2}-1 )*1} = \frac{ 2(x+1)-3(x-1)}{ x^{2} -1}  \\  \\  \frac{6-x^{2}+1 }{x^{2}-1 } = \frac{ 2x+2-3x+3}{ x^{2} -1}  \\  \\ 6- x^{2} +1=-x+5 \\  \\  x^{2} +x-2=0  \\  \\  D=1-4*(-2)= \sqrt{9} =3 \\  \\  x \frac{1}{2} = \frac{1 \neq 3}{2} =2;1 \\
Похожие вопросы
Предмет: Алгебра, автор: Aaaa123456ssss